European Constitutional Law Review - Eijsbouts, W.T.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
The European Constitutional Law Review (EuConst), a peer reviewed English language journal, is a platform for advancing the study of European constitutional law, its history and evolution. Its scope is European law and constitutional law, history and theory, comparative law and jurisprudence. Published triannually, it contains articles on doctrine, scholarship and history, plus jurisprudence and book reviews. However, the premier issue includes more than twenty short articles by leading experts, each addressing a single topic in the Draft Constitutional Treaty for Europe. EuConst is addressed at academics, professionals, politicians and others involved or interested in the European constitutional process. Its Editorial Advisory Board is composed of eminent members in the field of constitutional studies from across the Continent in its new EU format.
Keywords: Law -- Philosophy; Law; Private international law; Conflict of laws; International law; Comparative law; European Law; Private International Law, International & Foreign Law, Comparative Law; Theories of Law, Philosophy of Law, Legal History